Perancangan WebGIS sebagai Daya Tarik Destinasi Wisata Bahari di Raja Ampat - Fitriyani, Sakila Divia; Vinsa Qatrunnada; Dini Dwi Andini; M. Fahri; Lestari, Della Ayu; Silaban, Joy Elisabeth; Ramadhani, Tirta Samudera (Universitas Methodist Indonesia, 2024)
Indonesia, with 17,540 islands spread from Sabang to Merauke, is known as a maritime country with extensive natural potential, especially in marine tourism. One of the famous marine tourism potentials is Raja Ampat or known as